2020
DOI: 10.1021/jacs.0c10361
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Stereoselective P450 Enzyme BotCYP Enables the In Vitro Biosynthesis of the Bottromycin Core Scaffold

Abstract: Bottromycins are ribosomally synthesized and posttranslationally modified peptide natural product antibiotics that are effective against high-priority human pathogens such as methicillinresistant Staphylococcus aureus. The total synthesis of bottromycins

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The reaction mixture containing both epimerase BotH and P450 BotCYP led to the reaction to completion, rather than containing only BotCYP. The epimerase enzyme BotH first epimerizes the structures obtained by several enzymatic reactions, and then, BotCYP preferentially oxidatively decarboxylated the epimer containing d ‐aspartic acid (Adam et al, 2020). TbtJ1 and TbtJ2 could perform selective cyclopropanation of dehydroalanine residues within complex linear and cyclic RiPP cores in thiomuracin biosynthesis, which is another case of unusual reaction facilitated by P450 (Gober et al, 2017).…”
Section: Structure and Function Of P450s Involved In Antibiotics Bios...mentioning
confidence: 99%
“…The reaction mixture containing both epimerase BotH and P450 BotCYP led to the reaction to completion, rather than containing only BotCYP. The epimerase enzyme BotH first epimerizes the structures obtained by several enzymatic reactions, and then, BotCYP preferentially oxidatively decarboxylated the epimer containing d ‐aspartic acid (Adam et al, 2020). TbtJ1 and TbtJ2 could perform selective cyclopropanation of dehydroalanine residues within complex linear and cyclic RiPP cores in thiomuracin biosynthesis, which is another case of unusual reaction facilitated by P450 (Gober et al, 2017).…”
Section: Structure and Function Of P450s Involved In Antibiotics Bios...mentioning
confidence: 99%
“…30 Recently, BotCYP was reconstituted using three enzymes: BotCYP, BmCPR, and Fdx2 (from Bacillus megaterium 5 ) with substrate a/b (a = macroamidated, thiozoline product, b = epimerase, BotH-treated com-pound a) in the presence of NADPH resulting in a decarboxylated and oxidized reaction product with very poor yield (<25%). 28 To find a reason for low yield, equimolar mixture of L-Asp and D-Asp was used as a substrate and the product mixture was analyzed by LC-MS. Only D-Asp-containing substrate showed oxidative decarboxylation indicating that BotCYP preferentially accepts the D-isomer as a substrate. This confirmed that epimerization of L-Asp to D-Asp by epimerase BotH proceeds the BotCYP reaction.…”
Section: Oxidative Decarboxylation (Botcyp)mentioning
confidence: 99%
“…It indicates that during oxidative decarboxylation to the aromatic thiazole, the configuration of the C α -position of Asp7 was retained. 28…”
Section: Enzymology Of Bottromycin Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations